FORMULASI DAN UJI EFEKTIVITAS SEDIAAN EKSTRAK ETANOL KULIT PEPAYA (Carica papaya L) SEBAGAI BRIGHTENING GEL SERUM - Syafitri, Anggun; Sianipar, Masria Phetheresia; Fantika, Ardhana (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
Facial skin problems that often occur in women and adolescents are dull skin and dark looking skin. Papaya peel (carica papaya L) contains flavonoid compounds which function as antioxidants to brighten the skin. This study aims to formulate papaya peel extract into a serum gel dosage form and observe its effectiveness on the skin of volunteers for 4 weeks of treatment. The research was started by making papaya peel extract which was obtained by maceration method. Then the extract was formulated into serum gel preparations with varying concentrations of gelling agent Carbomer 940 4%, 5%, 6%. The preparations were eval_uated for their physical characteristics, namely organoleptic test, pH test, spreadability test, viscosity test, homogeneity test, irritation test, and test volunteer. The results showed that papaya peel extract could be formulated into a serum gel preparation that was homogeneous, light brown in color, had a spreadability of <5 cm, with a pH <6, and had a viscosity of >2000 cps. Serum gel formula containing Carbomer 940 with a concentration of 6% which has the best effectiveness.